Which domestic firms benefit from FDI? : evidence from selected African countries (UNIDO ViennaAT, 2013)
Analyses the main characteristics that can make domestic firms in Sub-Saharan Africa (net) winners of losers from the presence of FDI and explores the channels through which the multinational enterprises have an impact on the local firms' products, market, input availability and costs, access to finance, and export opportunities. Analyses the strategic reactions of domestic firms induced by the presence of foreign affiliates.
Keywords: PRODUCTIVITY